Stem cell transplantation for follicular lymphoma relapsed/refractory after prior rituximab: A comprehensive analysis from the NCCN lymphoma outcomes project. Issue 20 (6th August 2013) - Evens, Andrew M.; Vanderplas, Ann; LaCasce, Ann S.; Crosby, Allison L.; Nademanee, Auayporn P.; Kaminski, Mark S.; Abel, Gregory A.; Millenson, Michael; Czuczman, Myron S.; Rodriguez, Maria A.; Niland, Joyce; Zelenetz, Andrew D.; et al.
Abstract : BACKGROUND: Stem cell transplant (SCT)‐related outcomes and prognostication for relapsed/refractory follicular lymphoma (FL) are not well‐defined in the post‐rituximab era. METHODS: Through the National Comprehensive Cancer Network (NCCN) lymphoma outcomes study, 184 patients with relapsed/refractory FL who underwent autologous SCT (autoSCT) or allogenic SCT (alloSCT) following disease relapse after prior rituximab‐based therapy were examined. RESULTS: Patients who underwent autoSCT (N = 136) were older compared with patients who underwent alloSCT (N = 48) (54 versus 51 years, respectively, P = .01) and more frequently had grade 3 FL (35% versus 8%, respectively, P = .006). Patients who underwent alloSCT received more prior therapies (4 versus 3, respectively, P < .0001) and more often had resistant disease at SCT (19% versus 6%, respectively, P = .008). Cumulative 100‐day nonrelapse mortality (NRM) for autoSCT and alloSCT were 1% and 6%, respectively ( P < .0001), whereas 3‐year NRM rates were 3% versus 24%, respectively ( P < .0001). For autoSCT and alloSCT, cumulative rates of relapse, progression, and/or transformation were 32% versus 16%, respectively ( P = .03), whereas 3‐year overall survival rates were 87% versus 61% ( P < .0001); there were no differences in failure‐free survival. AlloSCT was associated with increased risk of death on multivariate analysis (hazard ratio = 2.77, 95% confidence interval = 1.46‐5.26, P = .002). This finding persisted on propensity scoring/matching. Multivariate analysis for autoSCT patients identified age > 60 years and > 3 prior therapies as adverse factors. Furthermore, a survival model was created for the autoSCT cohort based on number of factors present (0, 1, 2); 3‐year failure‐free survival was 72%, 47%, and 20%, respectively ( P = .0003), and 3‐year overall survival was 96%, 82%, and 62%, respectively ( P < .0001). CONCLUSIONS: AutoSCT remains an effective therapy for patients with FL. For alloSCT, continued strategies to reduce NRM are needed. Cancer 2013;119:3662–3671 . © 2013 American Cancer Society . Abstract : We identified several critical prognostic factors that predicted survival within and across autologous stem cell transplantation (autoSCT) and allogeneic SCT (alloSCT) cohorts and a prognostic survival model was created for patients with relapsed/refractory follicular lymphoma in the post‐rituximab era. Additionally, overall survival appeared improved for autoSCT versus alloSCT including on multivariate analysis and with propensity scoring/matching.